2020
DOI: 10.1371/journal.pone.0241564
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported musculoskeletal disorders of the hand and associated conducted therapy approaches among dentists and dental assistants in Germany

Abstract: Background Dental professionals are subjected to higher risks for musculoskeletal disorders (MSDs) than other professional groups, especially the hand region. This study aims to investigate the prevalence of hand complaints among dentists (Ds) and dental assistants (DAs) and examines applied therapies. Methods For this purpose, an online questionnaire analysed 389 Ds (240female/149male) and 406 DAs (401female/5male) working in Germany. The self-reported data of the two occupational groups were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
(75 reference statements)
0
14
1
Order By: Relevance
“…Here, too, the surveyed dentists mostly worked right-handedly and reported MSD more frequently for the right hand/wrist. While the study of Haas et al [ 53 ] shows a high prevalence, especially for the right wrist, the present analysis specifies a worse posture for the left wrist. This discrepancy can be explained by the fact that other risk factors than just the body posture favor the occurrence of MSD in dentistry; these include performing precise movements with the hands or carrying out repetitive tasks over a long period of time [ 54 ].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Here, too, the surveyed dentists mostly worked right-handedly and reported MSD more frequently for the right hand/wrist. While the study of Haas et al [ 53 ] shows a high prevalence, especially for the right wrist, the present analysis specifies a worse posture for the left wrist. This discrepancy can be explained by the fact that other risk factors than just the body posture favor the occurrence of MSD in dentistry; these include performing precise movements with the hands or carrying out repetitive tasks over a long period of time [ 54 ].…”
Section: Discussioncontrasting
confidence: 69%
“…This discrepancy can be explained by the fact that other risk factors than just the body posture favor the occurrence of MSD in dentistry; these include performing precise movements with the hands or carrying out repetitive tasks over a long period of time [ 54 ]. Since nearly all subjects were right-handed [ 53 , 55 ], the right hand holds the heavy, vibrating instruments and performs very precise fine motor movements. This fact, in addition to the ergonomics, increases the risk for MSD and is, thus, responsible for the higher prevalence of pain in the right wrist [ 53 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies compared actual students in different years of dentistry studies. In all the studies, women suffered from MSDs more often than men [ 3 , 8 , 9 , 14 , 15 , 16 , 20 , 23 , 25 , 26 , 27 , 28 , 29 , 34 , 35 , 36 ]. The most frequent areas of pain are neck, lower back, shoulders and hands [ 3 , 7 , 14 , 15 , 16 , 17 , 19 , 20 , 23 , 24 , 26 , 27 , 28 , 29 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have reported similar results among dental professionals. 2 , 7 , 32 The findings correlate with the fact that dental professionals mainly use the upper body regions when working. Disorders in the shoulder region may be correlated to the repetitive motions, vibration and long duration of the procedures, prolonged shoulder abduction (>45 â—¦ ) with elbow flexed and pronated with isometric and eccentric contraction, fatigue and strain deltoid, supraspinatus trapezius and serratus anterior.…”
Section: Discussionmentioning
confidence: 62%
“…4 Mainly involved regions of the body are the neck, lumbar back, shoulders and wrists. 2,[5][6][7][8] In the literature reported neck pain ranges from 20-84.9% and shoulder pain from 18.9-73.5%. 9 Similar results were documented by an earlier review, which focused on neck and shoulder disorders.…”
Section: Introductionmentioning
confidence: 99%